Damage Assessment of Reinforced Concrete Elements Due to Corrosion Effect Using Dynamic Parameters: A Review - Ivan Duvnjak; Ivan Klepo; Marijana Serdar; Domagoj Damjanović (Buildings, 2021)
Corrosion of reinforcement is one of the main problems related to the durability of reinforced concrete structures. This can cause cracks and a separation of the protective layer, as well as reducing strength and structural stiffness, which can result in numerous human casualties. Visual inspection is a standard method of assessing the condition of reinforced concrete structures whose limitations, such as time, interpretability, accessibility, etc., may affect its effectiveness. Therefore, damage determination methods based on dynamic parameters are becoming more and more prominent in the assessment of damage to reinforced concrete structures. The aim of this paper is to review the literature regarding the determination of corrosion of reinforcement by methods based on dynamic parameters, and to identify future research to develop a method that would detect corrosion problems in time through a continuous system of structural health monitoring.